The importance of cooperation between vocational schools and industry - İŞGÖREN, AYŞE NURİYE; ÇINAR, AYŞE; ORAL, BEKİR; ACAR BÜYÜKPEHLİVAN, GÜLHAN; ULUSMAN, LEYLA; ÖZNAZ, DEMET; POLAT, ZÜHAL; UZMANOĞLU, MUSTAFA SELÇUK (My University, 2009)
Technology takes place in every area of the daily life and its importance raise increasingly. For this reason; with the purpose of fitting to developing technologies; through the cooperation with industry, the education programs in vocational schools, which educate occupation, should be updated orderly. In this sense; who successfully gives education in between present facilities, and who refreshes itself according to new technologies to give more active and dynamic education; the Marmara University Vocational School of Technical Sciences started an infrastructural development project, to strengthen the cooperation between industries related to the programs in the vocational school. In the scope of the talked project; parallel to the developing technologies the subjects about; infrastructural development, making update on course name or course contents, developing laboratory and workshops’ technological infrastructure, developing training course facilities, building research-development center, and according to the practice ability of graduation projects in industry developing common goods takes place. In this study; the industry survey results according to the programs in vocational school related to industries is examined. Research results provided contribution to determine industries’ present situation and their expectations from vocational schools.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Technology; infrastructure; industry; cooperation; vocational school (VS)